Sintomas vocais, alterações da qualidade vocal e laríngea em professores: análise de instrumentos - Lima, Maria Fabiana Bonfim de (2008)
INTRODUCTION: Among voice professionals, teachers have been the focus of most studies in this area, probably due to the fact that this professional category represents, approximately 2.5 million people in Brazil, and also because these are the professionals who have been seeking Speech Therapy services for the longest period of time. Researches mention constant vocal illness in this professional group, which is pointed out as one of those with higher risk of developing functional vocal disorders. There are many researches from different regions of Brazil which dealt with profile tracing and risk factors for teachers, and used the questionnaire as the main instrument. In this manner, the perception of the vocal disorder is part of the teacher s own responsibility. However, few studies include a Speech Therapy and ENT doctor evaluations in order to relate this data. AIM: To identify the occurrence of vocal disorders, correlating aspects from self-perceptual, vocal quality and laryngeal evaluations of teachers of two public primary and secondary schools of the city of Sorocaba SP. METHODS: 60 teachers from both schools participated in this transverse observational-type study. The teachers filled out a self-perception questionnaire (adapted from FERREIRA et al., 2007), with questions regarding personal identification, functional status, and vocal aspects. Secondly, speech samples were collected (sustained vowel /a/, scaled vowel /a/ and spontaneous speech). Teachers also went through an endoscopic laryngeal evaluation. Three experienced Speech Therapists performed a vocal quality evaluation of the subjects using the GIRBAS scale to classify the voices as normal or altered, and to specify the degree of alteration. The ENT doctor used an evaluation protocol adapted from Oliveira (1999) to describe the presence or absence of laryngeal disorders. The chisquared association test and the Kappa agreement test were used for statistic evaluation of the collected data. RESULTS: 63,3% of the subject reported having vocal disorders in the present or past in self-perception evaluation; 43,3% were diagnosed with such disorder in Speech Therapy vocal quality evaluation and 46,7% received this diagnosis from the doctor s laryngeal examination. There was no association between self-perceptive and speech therapy or ENT evaluations. Furthermore, agreement was low amongst the three evaluations. However, there was statistic association between voice quality evaluation performed by the Speech Therapists and the laryngeal evaluation performed by the ENT doctor, with intermediate agreement between them. CONCLUSION: The prevalence levels of vocal disorders found in this population are alarming. The self-perception questionnaire showed greater sensibility to indicate prevalence of these disorders, and Speech Therapy evaluation proved itself to be more specific. To obtain a real diagnosis of the needs of the population receiving treatment, we suggest combining both instruments when implementing prevention programs with focus on this health issue